RESEARCH ON THE EFFECT TO THE EIGEN MODES AND EFFECT OF MINIATURIZATION OF THE METAL CAVITY RESONATORS PARTLY OCCUPIED BY A MAGNETIC-DIELECTRIC COMPOSITE MATERIAL WITH εr=10 AND μr=10 - XIAOWEI, WANG; JIN, PAN; PENGCHENG, LI (Journal of Mobile Multimedia, 2011)
This paper discuss the effect to the Eigen frequency of the metal cavity resonator partly occupied by magnetic-dielectric composite material by simulation and comparison, which is then used to assess the effect of miniaturization. Some important properties are found, which are useful for the miniaturization of passive devices for communication.